2018
DOI: 10.1016/j.jssc.2018.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis-dependent properties of barlowite and Zn-substituted barlowite

Abstract: The mineral barlowite, Cu 4 (OH) 6 FBr, has been the focus of recent attention due to the possibility of substituting the interlayer Cu 2+ site with non-magnetic ions to develop new quantum spin liquid materials. We re-examine previous methods of synthesizing barlowite and describe a novel hydrothermal synthesis method that produces large single crystals of barlowite and Zn-substituted barlowite (Cu 3 Zn x Cu 1−x (OH) 6 FBr). The two synthesis techniques yield barlowite with indistinguishable crystal structure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 37 publications
(74 reference statements)
2
40
0
Order By: Relevance
“…The onset of short range order is gradual but clearly becomes significant well below T = 16 K. For both 1 and 2, the entropy change associated with the magnetic transition is approximately 1/4 of the expected value for the four Cu 2+ s in the formula unit, implying that the interlayer Cu 2+ precipitates the order. (30) In an applied field, the transition broadens and shifts to lower temperature with a crossover at T ≈ 10 K, similar to the T N 1 of 2.…”
Section: As Shown Inmentioning
confidence: 59%
See 1 more Smart Citation
“…The onset of short range order is gradual but clearly becomes significant well below T = 16 K. For both 1 and 2, the entropy change associated with the magnetic transition is approximately 1/4 of the expected value for the four Cu 2+ s in the formula unit, implying that the interlayer Cu 2+ precipitates the order. (30) In an applied field, the transition broadens and shifts to lower temperature with a crossover at T ≈ 10 K, similar to the T N 1 of 2.…”
Section: As Shown Inmentioning
confidence: 59%
“…(33) Polycrystalline samples show no magnetic order, and a gapped ground state with Z 2 topological order has been proposed. (31,35,36) The first single crystals of Znsubstituted barlowite were recently synthesized with x = 0.33, which suppresses magnetic order to T = 4 K. (30) Our novel synthesis techniques produce large single crystals of barlowite and Zn-substituted barlowite, and measurements of the magnetic and structural properties allow for detailed studies of how the QSL tendencies on the S = 1 2 kagome lattice are affected by subtle structural symmetry-lowering and magnetic impurities on the interlayer sites.…”
mentioning
confidence: 99%
“…A closely related Cu(II) hydroxyl halide that has garnered considerable attention in the recent literature is barlowite, Cu 4 (OH) 6 FBr 19 , a naturally occurring mineral which has been synthetically produced by several groups [20][21][22][23][24][25] . A recent powder neutron diffraction (PND) study contributed to the ongoing debate around the nuclear and magnetic structures of this material 23 : like herbertsmithite, barlowite is formed from Cu 2+ S ¼ 1 2 kagomé layers but with a second interlayer Cu 2+ site, which is disordered at roomtemperature in the widely reported P6 3 /mmc model 20,21,24,25 . Below 250 K, one reported class of sample undergoes a subtle structural distortion to an orthorhombic Pnma phase 23 (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It has been theoretically suggested that Zn 2+ or Mg 2+ ions can replace the interlayer Cu 2+ in barlowite and thus dilute the AF order to give rise to a QSL state as in herbertsmithite 41,42 . While this proposal has been shown to succeed in Cu 3 Zn(OH) 6 FBr [26][27][28]39,43 , no Mgsubstituted barlowite has been reported. In this paper, we follow the same route in synthesizing the Znsubstituted barlowite to grow Mg-substituted barlowite.…”
Section: Introductionmentioning
confidence: 99%